La memoria histórica de la Guerra Civil, la dictadura franquista, y la Transición, en España. Síntesis histórica e iniciativas legislativas recientes - Pere Soler Paricio (Cahiers de Civilisation Espagnole Contemporaine)
This article surveys the historical memory of Spanish Civil War, Franco regime, and transition to democracy in Spain. First of all, it summarizes the topic from the last years of Franco regime to the sanction of the state and Catalan historical memory laws in 2007. Thereon, it deals both with the central government interruption of historical memory public policies from 2012 onwards, and the continuity of initiatives for remembering the past non related to the General State Administration. Finally, it analyses the historical memory laws that have been proposed, in some cases even approved, in several Spanish regional legislatures from 2016 to the beginning of 2018.